2019
DOI: 10.1111/bdi.12871
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography resting‐state spectral fingerprints distinguish bipolar depression and unipolar depression

Abstract: Objectives In clinical practice, bipolar depression (BD) and unipolar depression (UD) appear to have similar symptoms, causing BD being frequently misdiagnosed as UD, leading to improper treatment decision and outcome. Therefore, it is in urgent need of distinguishing BD from UD based on clinical objective biomarkers as early as possible. Here, we aimed to integrate brain neuroimaging data and an advanced machine learning technique to predict different types of mood disorder patients at the individual level. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Previous studies have reported significantly lower TCM syndrome scores in an acupuncture group compared to a fluoxetine group after 8 wk of treatment; a greater clinical efficacy was achieved with acupuncture treatment[ 19 , 20 ]. In addition, the incidence of adverse reactions in the acupuncture group (5.71%) was significantly lower than that in the fluoxetine group (25.71%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported significantly lower TCM syndrome scores in an acupuncture group compared to a fluoxetine group after 8 wk of treatment; a greater clinical efficacy was achieved with acupuncture treatment[ 19 , 20 ]. In addition, the incidence of adverse reactions in the acupuncture group (5.71%) was significantly lower than that in the fluoxetine group (25.71%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies on Rs-EEG oscillations, which have improved the diagnostics of MDD, the findings differ markedly and are partly contradictory. For example, compared to HC subjects, an EEG study reported increased γ in the frontal and temporal regions in MDD patients under the EC condition [31], whereas MDD patients showed no significant difference in the γ band under the EC condition in another work [32]. Previous studies have identified a frontal α asymmetry in MDD.…”
Section: Introductionmentioning
confidence: 93%
“…Result: PS was significantly reduced in left motor and preSMA of MDD patients in both beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and low gamma bands. Compared to the HC group, the MDD group demonstrated higher connectivity between lM1 and preSMA in the beta band (t = 3.214, p = 0.002, FDR corrected) and showed reduced connectivity between preSMA and rIFG in the low gamma band (t = −2.612, p = 0.012, FDR corrected).…”
mentioning
confidence: 93%
“…Connections between lM1, preSMA, and rIFG have been widely demonstrated to be associated with inhibition mechanisms (6,(14)(15)(16). MDD show abnormal PS in the beta and gamma bands compared to healthy controls (HC) (27,28). Authors of previous studies have demonstrated that the FC and PS in the beta and gamma bands among these regions may be a strong indicator of cognitive deficit in depression (25,26,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%